Macrocytic anemia, kidney dysfunction, and mortality in general population: Japan specific health checkup study - Yoichiro Otaki; Tetsu Watanabe; Tsuneo Konta; Masafumi Watanabe; Koichi Asahi; Kunihiro Yamagata; Shouichi Fujimoto; Kazuhiko Tsuruya; Ichiei Narita; Masato Kasahara; Yugo Shibagaki; Kunitoshi Iseki; et al. (Scientific Reports)
Abstract Anemia and chronic kidney disease (CKD), which worsen bidirectionally, are associated with mortality in older adults. This study aimed to examine the association between CKD and the type of anemia and its impact on mortality in the general population. Data from a nationwide database of 203,280 individuals who participated in the annual “Specific Health Check and Guidance in Japan” evaluation between 2008 and 2011 were used. Over a follow-up period of 4 years, 2,819 all-cause, 1,595 cancer-related, 523 cardiovascular, and 128 infectious disease deaths were recorded. Macrocytic anemia was detected in 2.3% of participants. The prevalence of normocytic and macrocytic anemia increased with advancing CKD stage. Multivariate Cox proportional hazards regression analysis revealed significant associations between macrocytic anemia and the all-cause, cancer, and cardiovascular mortality rates. Including the anemia type improved the prediction accuracy for all-cause deaths. The participants were divided into eight groups based on the anemia type and CKD. Macrocytic anemia of CKD had the highest hazard ratio for all-cause mortality in the general population. A correlation was observed between macrocytic anemia and CKD. Macrocytic anemia predicted mortality in the general population, suggesting that it could serve as an early indicator of premature death in high-risk individuals.